Using data digits to identify fabricated data. - Walter, C.F.
In this article we discuss four cases of research misconduct reported by the Office of Research Integrity (ORI) at the U.S. Public Health Service (PHS) in the Federal Register, focusing on how ORI uses digits in data other than the leading digit as evidence that data is fabricated or falsified. In the next article of this series, we examine more closely the probative value of using significant digits in ORI's analysis
Keywords: Data digits; Extra terminal digit; Fabricated data identification; Inconsequential digits; Questioned data; Research misconduct; Rounding off; Uniform distribution test; Unlikely digit distributions